Integrasi Pembelajaran Sosial Emosional dalam Pendidikan Dasar: Strategi Meningkatkan Motivasi Belajar Peserta Didik - Hilman Yusri (Jurnal Pendidikan Tuntas, 2026)
This study aims to examine the influence of the implementation of Collaborative for Academic, Social, and Emotional Learning (CASEL) on elementary school students’ learning motivation through a literature review approach. The research was conducted by analyzing various scientific articles, national and international journals, and relevant references related to social-emotional learning in elementary education. Data collection was carried out through literature searches on Google Scholar, ScienceDirect, Springer, and SINTA-indexed journals published between 2014 and 2024. The data were analyzed using a thematic analysis approach to identify patterns, trends, and major findings from previous studies. The results of the study indicate that the implementation of CASEL has a positive impact on improving students’ learning motivation, classroom engagement, collaboration skills, emotional management, and character development. Furthermore, the integration of social-emotional learning creates a more inclusive, supportive, and conducive learning environment for both academic and non-academic growth. The findings confirm that CASEL should be integrated more systematically into elementary school learning processes to support holistic education and optimize students’ overall development. Therefore, teachers and educational policymakers are encouraged to strengthen social-emotional learning practices in order to improve educational quality and student well-being in elementary schools.